Molecular Characterization of Antibiotic Resistance Genes in Staphylococcus Isolated from Cell Phone Users' and Non- Users' Ears - Tayabe Avazzadeh; Abbas Ali Rezaeian; Shafie Ghorbani Tazhandarreh; Roohollah Zarei Koosha; Davood Ghorbani Tazhandarreh; Abdolhassan Doulah (Islamic Azad University, 2018)
Introduction: Resistance to macrolide can be created by erm genes in Staphylococcus. The aim of the current study was to determine whether or not cell phone use can result in the antibiotic resistance of 16S rDNA, Coa, ermA, ermB and ermC genes in Staphylococci isolated from cell phone users' and non- users' ears. Methods: A total of 150 isolates of Staphylococci were tested by the disk diffusion method. The isolates were examined by PCR for 16S rDNA, Coa, ermA, ermB and ermC genes. Results: According to PCR results, in two statistical societies, 65.33% cell phone users with positive Coa had only one erm, 33.33% cell phone non-users with negative Coa had only one erm and %1.34 had genes, whereas 24 % cell phone non-users with positive Coa had one erm, %44 cell phone non-users with negative Coa had one erm and 32% had a minority of genes. Results showed that 16S rDNA, Coa, ermA, ermB, and ermC genes in the cell phone users group were more prevalent than the other group in Staphylococci isolated from ears. Conclusion: It is revealed that the presence of 16S rDNA, Coa, and erms genes had a significant relation to erythromycin and methicillin. Detection of ermA, ermB and ermC plays crucial roles in the molecular mechanisms, epidemiology of the efflux pump and methylase erythromycin ribosome. Since antibiotic resistant Staphylococci isolates may mutate and prompt constitutive resistances it is suggested that inducible resistance test should be implemented on erythromycin resistant sensitive isolates to prevent treatment failures.